2023
DOI: 10.1186/s13148-023-01470-4
|View full text |Cite
|
Sign up to set email alerts
|

An epigenome-wide analysis of socioeconomic position and tumor DNA methylation in breast cancer patients

Abstract: Background Disadvantaged socioeconomic position (SEP), including lower educational attainment and household income, may influence cancer risk and outcomes. We hypothesized that DNA methylation could function as an intermediary epigenetic mechanism that internalizes and reflects the biological impact of SEP. Methods Based on tumor DNA methylation data from the Illumina 450 K array from 694 breast cancer patients in the Women’s Circle of Health Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…118,119 crucial to comprehend the role of GPR37 in peripheral cancers, as protein−protein interaction (PPI) analysis has revealed its involvement in a functional pathway that facilitates breast cancer metastasis to the brain and lungs. 120,121 Furthermore, analysis of the Cancer Genome Atlas and Oncomine databases has shown high expression of GPR37 in lung adenocarcinoma (LUAD), with upregulation associated with unfavorable outcomes. 122,123 Gain-or LOF assays have demonstrated that increased GPR37 expression enhances the activation of TGF-β1, Smad2, and Smad3 phosphorylation, leading to improved proliferation, migration, and invasion of carcinoma cells in vitro.…”
Section: Relevance Of Gpr37 Heteromericmentioning
confidence: 99%
See 1 more Smart Citation
“…118,119 crucial to comprehend the role of GPR37 in peripheral cancers, as protein−protein interaction (PPI) analysis has revealed its involvement in a functional pathway that facilitates breast cancer metastasis to the brain and lungs. 120,121 Furthermore, analysis of the Cancer Genome Atlas and Oncomine databases has shown high expression of GPR37 in lung adenocarcinoma (LUAD), with upregulation associated with unfavorable outcomes. 122,123 Gain-or LOF assays have demonstrated that increased GPR37 expression enhances the activation of TGF-β1, Smad2, and Smad3 phosphorylation, leading to improved proliferation, migration, and invasion of carcinoma cells in vitro.…”
Section: Relevance Of Gpr37 Heteromericmentioning
confidence: 99%
“…A multiomics pilot study using mass spectrometry on cerebrospinal fluid (CSF) from recurrent MB patients revealed the upregulation of GPR37, as well as ADAMTS1 and GAP43 indicating the presence of hypoxic conditions, in the CSF of these patients . Functional studies have demonstrated that elevated levels of GPR37 promote tumor cell proliferation, migration, and invasion, while suppressing GPR37 through knockdown techniques inhibits malignant behaviors. , GPR37 is crucial to comprehend the role of GPR37 in peripheral cancers, as protein–protein interaction (PPI) analysis has revealed its involvement in a functional pathway that facilitates breast cancer metastasis to the brain and lungs. , …”
Section: Gpr37 Signaling and Functionmentioning
confidence: 99%